BOARD – CEO RELATIONSHIPS (ONE TIER SYSTEM – ANGLO SAXON) HUBUNGAN DEWAN KOMISARIS - DEWAN DIREKSI (TWO TIER SYSTEM CONTINENTAL) - Agus - Saptono (Universitas Slamet Riyadi, 2014)
GCG is a collection of laws, regulation and rules that must be full field to encourage, performance company sources work efficiently, generating long term, economic value that sustainable for our e holders and the communities. GCG implementation is expected to provide value added to the stakeholder of the company. In order to implement GCG companies are required should have independent director, audit committee and corporate secretary. The successful implementation of GCG for a company go public is highly dependent on the role of a company that consist of a general meeting of shareholder, director, and the board of commissioners. General meeting of shareholder as the supreme decision to determine; the direction Purpose and sustainability of the company; director are implementing operational and mandatory of shareholder and the commissioners a supervisory agency director. The relationship of the organs in the limited liability company has been organized in the form of legislation governing Limited Liability Company. This arrangement is a form of efforts to achieve Good Corporate Governance (GCG). Keywords: CEO relationships, one tier system, two tier system continental